Analisis Kepuasan Kerja Karyawan Pada PT. Niramas Utama Pontianak - Samosir B31106192, Nelson Lorensius Hasudungan (Jurnal Manajemen Update, 2014)
Every  company wants  all  employees who  work  can  do  his job  with full responsibility, so as to achieve the company's goal is to increase corporate profits hash. In order to achieve this, employees are expected to have high productivity.  In order to achieve high employee productivity, then the company must meet the level of employee satisfaction. Similarly, the company PT. Main Niramas Pontianak engaged in the field of food  and  drink  aloevera.  This  study  was  conducted  to  analyze  the  Employee · Satisfaction At PT. Main Niramas Pontianak. To further clarify this study examines the 7 variables that affect the job  satisfaction of employees at PT. Main Niramas Pontianak  ie, remuneration I salary, job  placement, job  severity, atmosphere and working environment, tools that support the occupation,  the attitude of the leadership and the nature of the work, monotonous or not. Of all the questions that researchers have provided in the form of a questionnaire given to all employees of all the question is a combination. The hash is obtained from the study of job satisfaction there is satisfied with what is obtained now and there are those who feel less satisfied with what has been obtained. However, the employee would be expected by a change in the future more attention to the welfare of employees as a whole. The results of this study are expected to help the leaders of PT. Main Niramas Pontianak to pay attention to the problems faced by the employees. In its effort to produce  food and  drink  aloevera, the  role  of  labor  is  very  important,  especially workers who have very high job satisfaction will increase the productivity of peak